Understanding species responses in a changing world by examining the predatory behaviour of southern calamari to changes in temperature - Patricia Peinado; Quinn P. Fitzgibbon; Jayson M. Semmens; Sean Tracey; Gretta T. Pecl (Frontiers in Marine Science, 2023)
Predator–prey interactions are key drivers in structuring communities, with the potential to substantially impact the whole ecosystem when important predators and prey are involved. Squid are voracious predators and also important prey for other top predators. To date, the available data suggests that under current and projected ocean warming, the behaviour of ectotherms could be modified (for example, through individual movement, predator avoidance and escape speed), yet little is known of the influence of temperature on the predatory behaviour of cephalopods. Here, the predatory behaviour of adult southern calamari (Sepioteuthis australis) under different thermal scenarios was examined demonstrating that squid exhibited different behaviour and performance capabilities across temperature treatments. Overall, attempts of squid to capture prey were faster and more persistent at higher temperature treatments (25°C), suggesting that individuals need to increase their food consumption rate, presumably associated with the higher energetic costs of living at elevated temperatures. However, we also observed a possible decrease in capture efficiency and increased prey handling time at higher temperatures suggesting that implications for energetic balance are not straightforward and that trade-offs need to be carefully explored. As cephalopods are ecologically important species acting as key links in food webs around the world, the results here could have important implications for the dynamics of many marine ecosystems in future.